Tissue flossing of the thigh increases isometric strength acutely but has no effects on flexibility or jump height - Konrad, A.; Bernsteiner, D.; Budini, F.; Reiner, M. M.; Glashüttner, C.; Berger, C.; Tilp, M. (European Journal of Sport Science, 2021)
The purpose of this study was to investigate the effects of a single floss band treatment of the thigh on hip and knee range of motion (ROM), knee extensor passive resistive torque (PRT), knee extensor maximum voluntary contraction (MVC) torque, and countermovement jump (CMJ) height.